Hot Topics and Frontier Evolution of Formation Control Research in Multiple Robots - Yong Xu; Malathy Batumalay; Choon Kit Chan; Walton Wider; Kui Fu; Lingmin Yang; Jiansheng Peng (Journal of Robotics)
This research conducts an extensive bibliometric analysis of the literature on the formation control of multiple robots. The main objective is to offer a comprehensive analysis of the present condition and future potential of this area. To accomplish this, this research employs a bibliometric methodology to examine current research trends and forecast future developments. This research gathered a total of 1656 journal articles from the Web of Science (WoS) database. The research utilizes bibliographic coupling and keyword co-occurrence analyses to identify influential publications, delineate the knowledge structure, and forecast the future trends. The bibliographic coupling analysis yielded four separate clusters, while the keyword co-occurrence analysis revealed four clusters. Although the importance of formation control research in multiple robots is growing, more scholarly effort is necessary to fully understand the academic panorama. The article provides significant insights into the rapidly expanding field of formation control in multiple robots. Furthermore, it offers a thorough examination of formation control research in diverse robots and emphasizes its potential for ongoing advancement.